2009
DOI: 10.1007/s11195-009-9123-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality of 15/16-Year-Old Girls and Boys With and Without Modest Disabilities

Abstract: Girls and boys with disabilities, 15-16 years of age, report a significantly higher rate of sexual debut than adolescents with no disabilities. In a society where a young person with a disability often is considered to have an essentially asexual status, there can be several fronts for adolescents to fight. The survey Life and Health-Young People 2005 was completed by 3,084 adolescents attending mainstream schools in Sweden. In this study the sexual debut in girls and boys with and without disabilities is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
(33 reference statements)
0
9
0
6
Order By: Relevance
“…On the other hand, they did not talk much about sexuality, even though sexual activity occurs early among young people with mild disabilities in Sweden and that sexuality was reported as an important area in which to participate in the community (Brunnberg et al . ). However, Wiegerink et al .…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, they did not talk much about sexuality, even though sexual activity occurs early among young people with mild disabilities in Sweden and that sexuality was reported as an important area in which to participate in the community (Brunnberg et al . ). However, Wiegerink et al .…”
Section: Discussionmentioning
confidence: 97%
“…The two subgroups were not found to be different in that respect, the reported feelings were mostly positive in both of them. It is possible that disabled women find their sex life satisfactory despite hip pain and other physical problems [4, 48]. Earlier studies show, however, that some behaviors, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Kempton and Stiggall (1989) suggested that sex education is essential for children with ID, as it provides a basis of knowledge and skills that enhance quality of life and aids in tbe prevention of deleterious experiences associated with sexual activity and the broader implications of being aware of sexuality issues (see also Smart, 2009). As indicated by previous studies, individuals with developmental disabilities including ID are at a greater risk of being sexually abused (e.g., Baladerian, 1991;Brunnberg, Bostrom, &. Berglund, 2009;Hershkowitz, Lamb, & Horowitz, 2007;Levy &.…”
mentioning
confidence: 86%